The Impact of Corporate Financial Resilience And Macroeconomic Fundamentals on Stock Price Volatility With The Variable Moderation of The Covid 19 Pandemic in The Infrastructure And Telecommunications Sector - Trias Andriyanto (Syntax Corporation, 2022)
This study aims to analyze the effect of corporate financial resilience and macroeconomic fundamentals on stock price volatility during the COVID-19 pandemic, focusing on the infrastructure and telecommunications sectors. The COVID-19 pandemic has significantly affected global economic conditions and financial markets, including the stock market. This study uses regression analysis methods to examine the relationship between corporate financial resilience (as measured by Current Ratio, Debt to Equity Ratio, and Return on Equity) and macroeconomic fundamentals (as measured by interest rates and Gross Domestic Product) to stock price volatility in the infrastructure and telecommunications sectors. The data used are historical stock price data and company financial data related to the COVID-19 pandemic period. The results show that Return on Equity (ROE) has a significant influence on stock price volatility in the infrastructure sector, while interest rates have a significant influence on stock price volatility in the sector. However, in the telecommunications sector, there are no variables of financial resilience or macroeconomic fundamentals that have a significant influence on stock price volatility. These results provide important insights for investors and companies in managing risk and making investment decisions during pandemic crises such as COVID-19.